Children's participation in brand‐based social networks: examining the role of evaluative social identity, self‐esteem and anticipated emotions on commitment and desire to recommend. (September 2016) - Hook, Margurite; Baxter, Stacey; Kulczynski, Alicia
Abstract: Social networks involving the social interactions and personal relationships of brand devotees (brand‐based social networks) are valuable company and marketing resources, playing a major role in brand and product promotion, and facilitating word‐of‐mouth. This research sought to examine the influence of evaluative social identity on brand‐based social network commitment and network recommendations, specifically for children. The sample for the study comprised 394 Australian children, 6–14 years of age, who participate in an informal offline social network for the brand 'Minecraft'. This research introduces anticipated emotions (positive and negative) as the mechanisms underlying the influence of evaluative social identity on brand‐based social network commitment and network recommendations. Specifically, when children are unable to participate in the brand network, they will experience negative emotions. When children are allowed to participate positive emotions are experienced. These emotions, both positive and negative, are found to enhance children's commitment to the brand‐based social network and also their desire to refer the network to non‐members. Further, this research provides evidence that the relationship between evaluative social identity, and both network commitment and network recommendations, is only observed for children with low personal self‐esteem. This research provides unique insight into the under‐researched area of children and brand‐based social networks, and introduces new moderating and mediating effects on established relationships, with findings useful for both academics and practitioners.